2018
DOI: 10.1071/rd17095
|View full text |Cite
|
Sign up to set email alerts
|

Mouse double minute homologue 2 (MDM2) downregulation by miR-661 impairs human endometrial epithelial cell adhesive capacity

Abstract: Human blastocysts that fail to implant following IVF secrete elevated levels of miR-661, which is taken up by primary human endometrial epithelial cells (HEECs) and impairs their adhesive capability. MicroRNA miR-661 downregulates mouse double minute homologue 2 (MDM2) and MDM4 in other epithelial cell types to activate p53; however, this has not been examined in the endometrium. In this study MDM2 protein was detected in the luminal epithelium of the endometrium, the site of blastocyst attachment, during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The xCELLigence technology which incorporates real-time monitoring of cell adhesion is also used as an approach to determine endometrial cell adhesive capacity (46). In this assay, endometrial epithelial cells adhesion is measured either directly on attachment to plastic plates or the plates are coated with various extracellular matrix (ECM) proteins and endometrial epithelial cell adhesion measured via electrical impedance in realtime (75). The TER assay is used to measure the integrity of interepithelial cell-tight junctions in vitro (44).…”
Section: In Vitro Assays Used To Investigate Plasma Membrane Transformentioning
confidence: 99%
“…The xCELLigence technology which incorporates real-time monitoring of cell adhesion is also used as an approach to determine endometrial cell adhesive capacity (46). In this assay, endometrial epithelial cells adhesion is measured either directly on attachment to plastic plates or the plates are coated with various extracellular matrix (ECM) proteins and endometrial epithelial cell adhesion measured via electrical impedance in realtime (75). The TER assay is used to measure the integrity of interepithelial cell-tight junctions in vitro (44).…”
Section: In Vitro Assays Used To Investigate Plasma Membrane Transformentioning
confidence: 99%
“…A panel of miRs will likely to be included, with the functional consequence of each individual miR on implantation being confirmed in ideally both humans ( in vitro ) and preclinical animal models ( in vivo ). Detailed functional studies have only covered a small proportion of miRs identified so far ( Table 2 ; Chu et al, 2015 ; Cuman et al, 2015 ; Kang et al, 2015 ; Kottawatta et al, 2015 ; Vilella et al, 2015 ; Zhang et al, 2015 ; Cai et al, 2016 ; Chen et al, 2016 ; Zheng et al, 2017 ; Sirohi et al, 2018 ; Winship et al, 2018 ; Balaguer et al, 2019 ; Griffiths et al, 2019 ; Takamura et al, 2019 ).…”
Section: Spent Blastocyst Culture Mediummentioning
confidence: 99%
“…There are many known regulators of human receptivity, including leukemia inhibitory factor (LIF) and interleukin 11 (IL-11) 710 , and more recently microRNA (miR) have been implicated to regulate endometrial receptivity and blastocyst implantation 11 . miR have been identified to be expressed and secreted by both human endometrium and blastocysts and consequently taken up by the opposite to have downstream effects on gene targets 1214 .…”
Section: Introductionmentioning
confidence: 99%